Actual Directions of Improving the the Content of Professional Training of the Future Pre-School Teachers: Present Social Order - Nelli Lysenko (Pedagogical Discourse, 2012)
The current aspect of improving of the content of students’ professional training in speciality “Preschool Education” by means of teaching Ukrainian ethnopedagogy is studied in the article. Some approaches to the interpretation of actual educational of upbringing of children  on the background of social order from  modern society are offered.